Liquidity, Information, and Infrequently Traded Stocks - EASLEY, DAVID; KIEFER, NICHOLAS M.; O'HARA, MAUREEN; PAPERMAN, JOSEPH B. (Journal of Finance, 1996)
ABSTRACT This article investigates whether differences in information‐based trading can explain observed differences in spreads for active and infrequently traded stocks. Using a new empirical technique, we estimate the risk of information‐based trading for a sample of New York Stock Exchange (NYSE) listed stocks. We use the information in trade data to determine how frequently new information occurs, the composition of trading when it does, and the depth of the market for different volume‐decile stocks. Our most important empirical result is that the probability of information‐based trading is lower for high volume stocks. Using regressions, we provide evidence of the economic importance of information‐based trading on spreads.